On the hydroid genus Sibogella Billard, 1911 (Cnidaria: Hydrozoa: Plumulariidae), with descriptions of two new species - Galea, Horia R.; Maggioni, Davide; Di Camillo, Cristina G. (Zootaxa, 2020)
The so far monotypic genus Sibogella Billard, 1911 is revised based on literature data. Its type species, S. erecta Billard, 1911, is thoroughly redescribed and illustrated, and accounts on two new congeners, S. flabellata sp. nov. from shallow waters of Indonesia and S. spissa sp. nov. from deep waters of New Caledonia, are provided. Single- (16S rRNA) and multi-locus (concatenated 16S, 18S, and 28S rRNA) phylogenetic assessments of the Plumulariidae, including newly-sequenced Sibogella material, supplement the alpha-taxonomical study.